Professor-avaliador: identidade deontológica e formação no contexto do sistema escolar - o caso do programa aprender pra valer - Silva, Esequias Rodrigues da (2014)
Various initiatives to external large-scale evaluation arise in Brazil during the 1990s, especially: National System of Basic Assessment (SAEB) and National Secondary Education Examination (ENEM). After more than twenty years since the birth of those initiatives, discussions about the schools own internal assessment by teachers have been intensified. Bringing near the outer large-scale evaluation to the school’s internal evaluation arises as a problem today in the Brazilian educational scenario. In this context, we have delimited the object of this research: the evaluator-teacher. We have defined as general objective of this research the discussion on the ethical identity of evaluator-teacher. The specific objectives that guided this study were planned as follows: (1) to discuss the ethical identity of evaluator-teacher in the context of the paradigm docimológico school evaluation, (2) to discuss the ethical identity of evaluator-teacher in the context of the pedagogical paradigm of school evaluation, (3) to identify the reference of powers attributed to the evaluator-teacher on Aprender pra valer (Learning for sure) program, by SEDUC-CE. This research falls under the qualitative approach by stating – among other features – the descriptive and interpretative matter, the interest on the use of the results, use various data sources. The methodological procedures substantiated in documentary analysis and literature review. The data were interpreted by content analysis. For purposes on this study we defined as theoretical references Bloom, Hastings and Madaus (1983), Perrenoud (1999), Afonso (2000), Hadji (1994.2001), Tyler (1949), Bonniol and Vial (2001). The survey results indicated that external evaluation on a large scale will influence on ethical identity of evaluator-teacher by proposing a framework for the construction of assessment instruments: the Reference Matrix. The Learning For Sure Program (Aprender Pra Valer) indicates the external evaluation on a large scale as the main agent of the management system, school management and the management of the classroom. However, this program does not have a specific project for the evaluator-teacher’s education evaluator and to confirm the importance of internal school evaluation. The docimologic paradigm allows us to identify the duties of the evaluator-teacher from the perspective of evaluation instruments. While the formation of the evaluator-teacher, based on educational paradigm, lies in their education in a complex frame of the systemic approach initially announced by Tyler (1977) and confirmed by Bloom, Hastings and Madaus (1983), Perrenoud (1999, 2000, 2002) and Hadji (1994,2001).